PECULARITIES OF FORMING A STRATEGY OF THE DEVELOPMENT OF ECO FRIENDLY AGRICULTURE IN UKRAINE IN THE CONDITIONS OF EURO-INTEGRATION PROSPECTS (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article analyzes possible ways of creating a strategy of the development of eco friendly agriculture in Ukraine and the prospects for its efficient functioning. At the present stage of development of land use agriculture of Ukraine has complex tasks for determining the ways of further development in the conditions of market relations. Nowadays, agricultural production in Ukraine is aimed at achieving maximum economic benefits without proper measures for increasing soil fertility and the expenses for protecting land resources. Due to the excessive load on land resources, a complex of global and regional environmental problems in agricultural production occurs, namely: loss of natural fertility of soils, their degradation, depletion, distribution of wind and water erosion, pollution of the environment by means of chemicals, radionuclides, heavy metals, wastes of animal husbandry, etc. Farmers, focusing on increasing profits, grow crops that are in demand, but neglect the principles of support of biodiversity. These significant violations in scientifically grounded crop rotations not only deplete the soils, but also increase the number of harmful organisms on agricultural lands. In addition, land degradation as a result of anthropogenic impact causes significant damage and is a burden for the economy of enterprises and the state as a whole. This leads to a deterioration of the quality of agricultural land. In order to ensure a balanced development of the economy and rational nature management, the transition of the agrarian sector of Ukraine’s economy to the model of sustainable development and further functioning on these bases is important.Therefore, the formation of a strategy for the development of eco friendly agriculture in Ukraine is urgent
Keywords: ecological safety, ecologization, eco friendly agriculture, strategy of development of eco friendly agriculture